Measuring self-reported polyvictimization in foster youth research: A systematic review. (September 2020) - Loomis, Alysse M.; Feely, Megan; Kennedy, Stephanie
Abstract: Background: Youth who are or have been in foster care (foster youth) are at higher risk for adverse outcomes in early adulthood. As the importance and complexity of victimization experiences, including types, timing, and perpetrators, is better understood it is unclear whether or to what extent the research on foster youth assesses polyvictimization. Because many types of victimization, such as community violence, are under-reported or absent in the administrative data typically used for research with foster care populations, self-reports of victimization experiences are necessary to comprehensively assess polyvictimization. Polyvictimization places youth at increased risk for adverse outcomes, and yet is not widely measured in the foster youth population. This is likely in part due to the wide-use of administrative reports to assess maltreatment among research on foster youth which does not capture a full range of victimization experiences. Objective: The aim of the present study was to systematically review and evaluate the measurement of self-reported polyvictimization with foster youth samples. Methods: A search in Academic Search Premier, MEDLINE, PsycARTICLES, Psychology and Behavioral Sciences Collection, Social Work Abstracts, SociINDEX, and Scopus was conducted. Articles included peer-reviewed, quantitative research studies that measured self-reported victimization (including violence exposure and/or maltreatment) with foster youth samples between 1997−2017. In total, 1887 studies were identified and reviewed by two raters and of those 18 met the study criteria. Results: Almost all of the included studies ( n = 16) measured multiple types of victimization through self-report. The most common types of victimization measured were sexual abuse ( n = 15), physical abuse ( n = 14), and physical neglect ( n = 11). Half of studies (n = 9) measured at least one non-maltreatment victimization experience, such as community violence exposure and/or dating violence. However, included studies rarely measured other aspects of victimization, such as timing of exposure (e.g., pre or during foster care), which research has identified as relevant to outcomes. Conclusions: This is the first systematic review to assess the measurement of self-reported polyvictimization in research with current or former foster youth. Given the limited comprehensive assessment of victimization, these findings support strong recommendations for developing or adapting polyvictimization measures specifically for foster youth so that the measures include child welfare-specific factors such as the timing and perpetration of victimization experiences.